2009
DOI: 10.1152/ajprenal.90774.2008
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of purinergic signaling in lithium-induced nephrogenic diabetes insipidus

Abstract: Zhang Y, Nelson RD, Carlson NG, Kamerath CD, Kohan DE, Kishore BK. Potential role of purinergic signaling in lithiuminduced nephrogenic diabetes insipidus. Am J Physiol Renal Physiol 296: F1194 -F1201, 2009. First published February 25, 2009 doi:10.1152/ajprenal.90774.2008.-Lithium (Li)-induced nephrogenic diabetes insipidus (NDI) has been attributed to the increased production of renal prostaglandin (PG)E2. Previously we reported that extracellular nucleotides (ATP/UTP), acting through P 2y2 receptor in rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 54 publications
(53 reference statements)
0
43
1
Order By: Relevance
“…This was found to occur without any alterations in serum or renal medullary lithium levels (41,42). The mechanisms are not completely understood, but our study suggested reduced PGE 2 signaling through the EP 3 receptor might play a role by preserving cAMP generation and thus protecting collecting duct AQP2 protein in the renal medulla (42).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…This was found to occur without any alterations in serum or renal medullary lithium levels (41,42). The mechanisms are not completely understood, but our study suggested reduced PGE 2 signaling through the EP 3 receptor might play a role by preserving cAMP generation and thus protecting collecting duct AQP2 protein in the renal medulla (42).…”
mentioning
confidence: 60%
“…Recently, we (41,42) have shown that mice with genetic deletion of P2Y 2 R have significant resistance to the development of lithium-induced polyuria. This was found to occur without any alterations in serum or renal medullary lithium levels (41,42).…”
mentioning
confidence: 99%
“…Thus, it appears that the autocrine and/or paracrine actions of extracellular nucleotides through P2Y receptors constitute tonic inhibitory effect on water and sodium reabsorption mediated by the AVP and aldosterone. Based on this deduction, we posited that the same actions of extracellular nucleotides mediated by P2Y receptors may also contribute to the development of collecting duct resistance to AVP often seen in acquired nephrogenic diabetes insipidus (NDI), such as the one induced by chronic lithium administration for the treatment of bipolar disorder [11][12][13]. Accordingly, we demonstrated that genetic deletion of P2Y 2 receptor confers significant resistance for the development of lithium-induced NDI [14,15].…”
Section: Introductionmentioning
confidence: 89%
“…However, despite major progress, no clear consensus regarding the "trigger" for the onset of the condition exists. For example, data from large-scale proteomic (7) and metabonomic approaches (8), coupled with targeted studies in animal models and gene-modified mice, have illustrated changes in renal prostaglandins (9); purinergic signaling (10); and the activity of glycogen synthase kinase 3 (GSK3) (11), PKC (12), MAPKs, ERKs ERK1/2 and P38α (13), and the phosphatidylinositol signalPsychiatric patients treated with lithium (Li + ) may develop nephrogenic diabetes insipidus (NDI). Although the etiology of Li + -induced NDI (Li-NDI) is poorly understood, it occurs partially due to reduced aquaporin-2 (AQP2) expression in the kidney collecting ducts.…”
Section: Introductionmentioning
confidence: 99%